ANALISIS FIQIH MUAMALAH KONTEMPORER DALAM TRANSAKSI JUAL BELI ONLINE - Syahrizal; Muhamad Zen (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAI ALMUSLIM, 2024)
Online buying and selling is currently very popular with all people who have internet access, because with all methods that in essence make it easier and present a sense of satisfaction so that online buying and selling is never avoided from the topic of conversation. Buying and selling before the advancement of technology already had standards in practice that had been regulated in the Qur'an and Al-Sunnah. So that however, technology changes the method of transactions, but Islam long before that has established signs that must be obeyed for believers. These signs have already existed with a legal basis, namely the Qur'an, Al-Sunnah and Ijma'. The Qur'an commands that if buying and selling in an initial contract provides relief for the buyer, namely by giving goods with a debt contract to write a grace period given to the buyer in paying it off. Al-Sunnah ordered not to sell goods that are different from those offered, thus giving rise to the nature of liars. And Ijma' Ulama ordered buying and selling so that there would be no ghoror, namely the ambiguity in the contract at the beginning of the transaction that there was no guarantee, in this case the buyer was deceived in the specifics of the goods and vice versa the seller was deceived in the value of an item.